Perceptions of ecosystem services and disservices of bamboo by indigenous communities in Northeast India - Rebecca Lalawmpuii Sailo; Biplov Chandra Sarkar; Khulakpam Apshahana; Aman Dabral; Ayang Jilen; Adela D. Marak; Gopal Shukla; C.P. Suresh; Sumit Chakravarthy (Advances in Bamboo Science)
This study documents and assesses the ecosystem services (ES) associated with bamboo species in Lohit District, Arunachal Pradesh, northeast India. Conducted between March 2021 and February 2022, the research employed a multistage random sampling method, selecting 10 respondents from each of 10 villages. Data were gathered through in-depth personal interviews with a semi-structured questionnaire to evaluate the socioeconomic status and perceptions of ecosystem services and disservices of bamboo among indigenous communities. The present study recorded seven bamboo species, viz., Bambusa tulda, Bambusa vulgaris, Dendrocalamus hamiltonii, Dendrocalamus giganteus, Bambusa bambos, Cephalostachyum sp. and Bambusa pallida. A total of 18 ecosystem services associated with these bamboo species were recorded, including provisioning services (10), regulatory services (6) and cultural services (2). Of all the ecosystem services, provisioning services were recorded as the most regularly used by the villagers in their day-to-day life. Some disservices of bamboo were perceived by the respondents, including reductions in crop yield, competition with NTFPs, reductions in aesthetic views, difficulties in accessing the forest, and attracting wild elephants. Despite these disservices, bamboo has a significant potential to enhance human well-being and improve the socio-economic conditions of the region. By serving as a sustainable alternative to concrete and steel, bamboo offers a wide range of ecosystem services, from provisioning to supporting, making it a valuable resource for sustainable development.